Cognitive and Emotional Engagement in Character Formation: A Phenomenological Study of School Family Synergy - Vinsensius Bawa Toron; Hermania Bhoki; Florens Maxi Un Bria; Fidelis Regi Waton (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study examines how character values are developed through cognitive and emotional engagement within school–family collaboration. It focuses on the roles of teachers, parental involvement, and student participation in supporting character formation. Methodology: A descriptive phenomenological design was used with nine purposively selected participants, including school leaders, teachers, parents, and students. Data were collected through interviews, observations, and documents, then analyzed thematically using ATLAS.ti 7. Credibility was ensured through triangulation and member checking. Main Findings: Teacher shape character through modeling and instructional guidance; parents reinforce values through example and communication; and students show engagement through reflection and cooperative behavior. Strong school family synergy shared routines, communication, and aligned expectations enhances character habituation, though challenges remain in teacher capacity, parental involvement, and cultural constraints. Cognitive and emotional engagement act as mediating processes in character formation and align with contemporary character education theories. The study also highlights a contextual gap in the existing literature, particularly the limited attention to culturally grounded and community-based approaches in character education. Novelty/Originality of this study: The study offers a culturally rooted phenomenological model integrating cognitive emotional engagement with school family collaboration. Policies should reinforce educator training, parental participation, and consistent value-based routines across home and school settings.